2020
DOI: 10.3389/fvets.2020.00392
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Pathological Study of the First Outbreak Cases of African Swine Fever in Vietnam, 2019

Abstract: African swine fever (ASF) is a devastating disease of swine and the most important disease for the pork industry. Since the outbreaks in 2007 in the Caucasian region, it has been spreading to the West and East quite swiftly. In this study we have analyzed the clinical signs and pathological features of the first outbreaks on ASF in Vietnam in 2019, caused by an isolate with 100% similarity to the genotype II (p72) isolates from Georgia in 2007 and China in 2018. The disease onset with a peracute to acute clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 44 publications
(56 reference statements)
5
23
0
2
Order By: Relevance
“…As of November 2020, ASF outbreaks have been reported in more than 20 of the country’s 63 provinces [ 9 ]. Several molecular and pathological studies on ASFV-infected pigs from ASF outbreak farms were conducted to evaluate the characteristic lesions and examine the genetic properties of ASFV strains from Vietnam [ 10 12 ]. Because no virus inoculation studies have been conducted to evaluate the virulence and pathogenicity of ASFV isolates from Vietnam, the pathogenicity of these strains is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…As of November 2020, ASF outbreaks have been reported in more than 20 of the country’s 63 provinces [ 9 ]. Several molecular and pathological studies on ASFV-infected pigs from ASF outbreak farms were conducted to evaluate the characteristic lesions and examine the genetic properties of ASFV strains from Vietnam [ 10 12 ]. Because no virus inoculation studies have been conducted to evaluate the virulence and pathogenicity of ASFV isolates from Vietnam, the pathogenicity of these strains is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Although clinical signs and lesions by ASFV have been recorded both in previous experimental and field studies (Schlafer and Mebus 1984, Kipanyula and Nong'ona 2017, Nga, Tran Anh Dao et al 2020, Yoon, Hong et al 2020, this is the first report of neurological signs in ASFV-infected neonate piglets. In these piglets, ASFV DNA and a significant amount of ASFV antigen and was found in brain tissues which showed microscopic lesions.…”
Section: Resultsmentioning
confidence: 76%
“…Based on the partial sequence of the p72 encoding gene (Bastos, Penrith et al 2003), 23 genotypes of ASFV have been identified. All of the ASFV reported in Viet Nam belong to genotype II (Le, Jeong et al 2019, Nga, Tran Anh Dao et al 2020, Tran, Truong et al 2020. Clinical signs of ASF vary from peracute to subacute depending on the virus virulence, the route of infection.…”
Section: Introductionmentioning
confidence: 99%
“…In many Asian countries, backyard and small-scale pig farms are in the majority, e.g., approximately 65% of the total pig population in Vietnam. This has provoked wide transmission of ASF and economical loss caused by the low biosecurity of these farms [ 41 42 ]. Recently there are some reports that animal industries are being transformed and upgraded.…”
Section: Change and Preparation Of Asf Outbreaks For The Futurementioning
confidence: 99%